MUI Fatwa on IVF and the Protection of Lineage and Children’s Rights - Arfah; Kurniati; Fatmawati (IAIN Parepare, 2026)
fertilization, has raised complex issues in Islamic family law. These issues are not limited to medical permissibility, but also involve lineage protection, children’s rights, embryo status, guardianship, and inheritance. This study aims to analyze the legal foundation of the Majelis Ulama Indonesia fatwa on in vitro fertilization and to assess its normative adequacy in responding to modern reproductive technologies through the framework of maqāṣid al sharī‘ah. This research uses library research with normative theological and maqāṣid al sharī‘ah approaches. Data were obtained from MUI fatwas, fiqh literature, books, peer reviewed journal articles, and academic studies on Assisted Reproductive Technology, then analyzed descriptively using a qualitative method. The findings show that MUI permits in vitro fertilization when sperm and ovum originate from a legally married couple and the embryo is implanted into the wife’s uterus. In contrast, sperm donation, ovum donation, and surrogacy are prohibited because they may lead to lineage confusion. From the perspective of maqāṣid al sharī‘ah, the fatwa is consistent with the protection of lineage, life, religion, and children’s rights. However, emerging issues such as cryopreservation, preimplantation genetic testing, genetic engineering, and embryo use after divorce or the death of a spouse indicate the need for more responsive ijtihad and legal guidelines in addressing contemporary reproductive bioethics.